Fuel treatments and landform modify landscape patterns of burn severity in an extreme fire event - Prichard, Susan J; Kennedy, Maureen C (Ecological applications, 2014)
Under a rapidly warming climate, a critical management issue in semiarid forests of western North America is how to increase forest resilience to wildfire. We evaluated relationships between fuel reduction treatments and burn severity in the 2006 Tripod Complex fires, which burned over 70 000 ha of mixed-conifer forests in the North Cascades range of Washington State and involved 387 past harvest and fuel treatment units. A secondary objective was to investigate other drivers of burn severity including landform, weather, vegetation characteristics, and a recent mountain pine beetle outbreak. We used sequential autoregression (SAR) to evaluate drivers of burn severity, represented by the relative differenced Normalized Burn Ratio index, in two study areas that are centered on early progressions of the wildfire complex. Significant predictor variables include treatment type, landform (elevation), fire weather (minimum relative humidity and maximum temperature), and vegetation characteristics, including canopy closure, cover type, and mountain pine beetle attack. Recent mountain pine beetle damage was a statistically significant predictor variable with red and mixed classes of beetle attack associated with higher burn severity. Treatment age and size were only weakly correlated with burn severity and may be partly explained by the lack of treatments older than 30 years and the low rates of fuel succession in these semiarid forests. Even during extreme weather, fuel conditions and landform strongly influenced patterns of burn severity. Fuel treatments that included recent prescribed burning of surface fuels were particularly effective at mitigating burn severity. Although surface and canopy fuel treatments are unlikely to substantially reduce the area burned in regional fire years, recent research, including this study, suggests that they can be an effective management strategy for increasing forest landscape resilience to wildfires.